A novel ATR‐FTIR technique for identifying colloid composition in natural waters. Issue 6 (8th July 2014) - McGuire, Molly M.; Herman, Ellen K.
Abstract Although understanding colloid composition has been frequently cited as essential to predicting contaminant transport in natural waters, most current methods to collect and identify colloid composition chemically alter the colloids prior to analysis and fail to identify colloid mineralogy and organic components. This paper presents a new, low‐cost method employing attenuated total reflection Fourier transform infrared spectroscopy (ATR‐FTIR) to identify colloids including organic material in concentrated suspensions. The concentration method employing tangential ultrafiltration at a steady temperature prevents redistribution of dissolved phase and suspended sediments into the colloidal fraction through post‐sampling reactions. ATR‐FTIR allows for direct analysis of concentrated suspensions rather than requiring drying that may alter composition in the colloidal phase, for example, by precipitating carbonates in samples from karst waters. The ability of this technique to monitor variation in colloidal composition is demonstrated through the examination of colloids under two different flow conditions in a karst aquifer and the West Branch of the Susquehanna River in Central Pennsylvania. Copyright © 2014 John Wiley & Sons, Ltd.